KESTABILAN GLOBAL TITIK EQUILIBRIUM MODEL DASAR INFEKSI VIRUS UNTUK HEPATITIS B - Susanto, Andi (IAIN Batusangkar, 2012)
In this paper it is considered about Amanded Basic Virus Infection Model (ABVIM), with defined R0 which is free from carrying capacity. R0 makes ABVIM reasonable for interpreting Hepatitis B virus infection. The behaviour of stability of ABVIM in free virus equilibrium point with R0 less than one and endemic equilibrium point more than one is given with numerical simulation.Key words: Basic virus infection model, Hepatitis B virus infection, equilibrium point, stability